2011
DOI: 10.1021/nl203975u
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Resolution Spectroscopic Imaging of Ensembles of Nanocatalyst Particles Across the Life of a Fuel Cell

Abstract: * These authors contributed equally to this work.The thousandfold increase in data-collection speed enabled by aberration-corrected optics allows us to overcome an electron microscopy paradox -how to obtain atomic-resolution chemical structure in individual nanoparticles, yet record a statistically significant sample from an inhomogeneous population. This allowed us to map hundreds of Pt-Co nanoparticles to show atomic-scale elemental distributions across different stages of the catalyst aging in a proton-exch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
4
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(198 citation statements)
references
References 44 publications
15
174
4
5
Order By: Relevance
“…Next, we verified the core-shell elemental distribution of individual particles at the atomic scale using various (scanning) transmission electron microscopy ((S)TEM) techniques, including a high-angle annular dark field (HAADF)-STEM and electron energy loss spectroscopy (EELS) 32 . Figure 4a shows the intensity profiles in a line scan across a sphere-like Ru@Pt NP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we verified the core-shell elemental distribution of individual particles at the atomic scale using various (scanning) transmission electron microscopy ((S)TEM) techniques, including a high-angle annular dark field (HAADF)-STEM and electron energy loss spectroscopy (EELS) 32 . Figure 4a shows the intensity profiles in a line scan across a sphere-like Ru@Pt NP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dissolution of Pt from small Pt-alloy nanoparticles will cause it to redeposit onto larger nanoparticles, where it forms a thick shell on an alloy core. 150,151 This reduces the solute metal content, resulting in a decrease in specific activity. Presumably this is either due to strain relaxation 74 or due to a decreased subsurface solute metal content.…”
Section: Nanoparticulate Pt-alloy Catalystsmentioning
confidence: 99%
“…Nonetheless, several research groups have reported the synthesis of ''Pt-skin'' structures upon carbon-supported Pt-alloy nanoparticles. 90,151,168,169 They achieved this either through hightemperature annealing in an inert or reducing atmosphere or by electrochemical cycling in a CO-saturated electrolyte. Each of these studies demonstrated a higher ORR activity than for a standard leached ''Pt-skeleton'' catalyst.…”
Section: Strategies To Improve the Performance Of Pt-alloy Nanoparticlesmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] However, in the harsh acidic and oxidising environment of a fuel cell, these alloys degrade by dealloying. [39][40][41] In our laboratory we have taken a different approach, namely to study alloys of Pt and rare earths such as Y, Gd, Ce and La. 33,[42][43][44][45][46][47][48] These alloys have a particularly negative heat of formation, which should provide them with long term-kinetic stability against dealloying at the cathode of a fuel cell.…”
Section: Introductionmentioning
confidence: 99%